Kinetics and Thermodynamics Study of Ammonia Leaching on Spent LMR-NMC Battery Cathodes - Perdana, Indra; Rahman, Muhammad Irfan; Aprilianto, Doni Riski; Petrus, Himawan Tri Bayu Murti; Kinanti, Divita Hayyu (Indonesian Journal of Chemistry, 2024)
The recycling of spent lithium NMC-type batteries, widely used in electric vehicles, presents a challenge due to manganese content, which complicates metal separation and purification. This study explored a selective leaching process using ammonia to recover metals from high-manganese-content LMR-NMC cathodes. By adjusting the (NH4)2SO4 reagent concentration to 1–2 M and maintaining the temperature between 50–80 °C, the recovery rates of lithium, nickel and cobalt metals were enhanced, leaving manganese primarily as residue in the form of Mn(OH)₂ and (NH4)2Mn(SO4)2. A kinetics model, integrating an equilibrium-shrinking core model with a modified temperature-dependent Arrhenius approach, accurately simulates the metal recovery. The activation energies of the forward leaching reactions of Li, Ni, and Co were respectively (1.4331±0.0036)×105, (1.5494±0.0034)×105, and (1.5743±0.0040)×105 J/mol, while those for the backward reactions were (5.3307±0.0041)×105, (2.4753±0.0093)×105, and (1.6289±0.0092)×105 J/mol, respectively. The leaching mechanism was found to be exothermic, which allows maximum recovery at low temperatures. The findings highlight ammonia’s effectiveness as a selective leachant, significantly reducing manganese in the leaching solution, and streamlining nickel and cobalt separation, thus enhancing the recycling process’s efficiency and sustainability.